2019
DOI: 10.1039/c9cy01189g
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric active site modification observed by alkali ion titrations of Sn-Beta

Abstract: Titrations and functional assays are combined to gain insight into the stoichiometric correlations for alkali ions and the tin active sites in Sn-Beta, and show that three different states with distinct catalytic properties exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Previous studies have shown how the addition of small quantities of alkali salts can improve the selectivity of certain Sn-Beta catalysts toward retro-aldol fragmentation. 12 , 21 , 22 , 30 , 55 It has been proposed that the effect of alkali salts arises from their ability to exchange protons present in the active site environment, thereby minimizing the partial Brønsted acidity of Sn-Beta materials and favoring the retro-aldol fragmentation pathway. 21 , 55 However, the susceptibility of different preparations of Sn-Beta catalysts for the alkali effect in continuous flow has not yet been evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown how the addition of small quantities of alkali salts can improve the selectivity of certain Sn-Beta catalysts toward retro-aldol fragmentation. 12 , 21 , 22 , 30 , 55 It has been proposed that the effect of alkali salts arises from their ability to exchange protons present in the active site environment, thereby minimizing the partial Brønsted acidity of Sn-Beta materials and favoring the retro-aldol fragmentation pathway. 21 , 55 However, the susceptibility of different preparations of Sn-Beta catalysts for the alkali effect in continuous flow has not yet been evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon seems to be related to a saturation effect of the tin catalytic sites with K + ions, blocking the access of the monosaccharide substrates to Sn sites and thus reducing the catalytic efficiency of the materials in retro-aldol condensation transformations. 35 …”
Section: Resultsmentioning
confidence: 99%
“…MCM-48, instead, is typically prepared in mixtures rich in sodium or potassium, which remain on the surface of the material . For the isomerization of glucose, it is well-known that the presence of these cations affects the reaction mechanism. ,,, To highlight the presence of the cation, the materials were named K + /Sn-MCM-48. Note that this is a typical MCM-48 and has not undergone any modification (except for the introduction of Sn).…”
Section: Resultsmentioning
confidence: 99%